Il maharaja, l'elefante e la qualità dell'(e)Learning - Patrizia Maria Margherita Ghislandi; Juliana Elisa Raffaghelli (LED Edizioni Universitarie, 2014)
(The Maharaja, the Elephant and the Quality of (e)Learning) Starting from a metaphor coming from the story «The six blind men and the elephant», this paper introduces the most significant results of a study carried out over the last ten years on the topic of the quality of (e)Learning. Overall, it focuses on the four levels through which quality can be analyzed: epistemological, theoretical, methodological and of method. Furthermore, it identifies the categories that constitute the basis of such an analysis: dimensions, levels, stakeholders and time. Accordingly, the paper highlights the characteristics of the quality of (e)Learning on the basis of the authors' empirical research work: the term «mediated quality» is presented as a concept that encompasses a participatory, trans/formative and open quality. Therefore, the paper illustrates the specific results, from the processes to the instruments adopted to mediate the quality of the empirical study,. The authors come up with the following reflection: if the quality of (e)Learningif is to be based on a constructivist epistemology, a pedagogical vision and a mixed methodological approach with a strong qualitative orientation, and if quality is to be mediated with instruments that enhance participation, transformation and openness, then a scholarship, iterative, participatory, open and eclectic learning design is required. To conclude, the authors hope, with the maharaja of the story, that research collaboration, as proposed in this paper, will lead to improve further results regarding the quality of (e)Learning.